Harriet Prescott Spofford’s Development of a Protestant Aesthetic for a Diverse Nation - Paula Kot (European Journal of American Studies)
In “Charlestown,” an historical sketch from her 1871 collection New-England Legends, Harriet Prescott Spofford examines the contest between Protestantism and Roman Catholicism that shaped Americans’ understanding of democracy as well as Spofford’s understanding of her role as an author in an increasingly heterogeneous nation. The sketch focuses on the 1834 burning of the Ursuline Convent and School of Mount Benedict in Charlestown, Massachusetts, by a Protestant mob, an assault that affords Spofford the opportunity to examine the nation’s ability to accommodate difference of all kinds. Spofford adopts a Protestant aesthetic in order to free readers from entrenched bigotry and unify an increasingly diverse nation. She develops a participatory model of creating consensus in an expanding nation that replicates the dynamic of democracy in the public sphere. Spofford’s understanding of the role she plays in the process of imperialism as a woman writer, as well as her sincere efforts to combat bigotry in herself and in her world, require us to reassess her place within the ranks of nineteenth-century American women writers.